Ruthless - Showalter, Gena (Showalter, Gena. Immortal enemies novels, 2022)
Micah the Unwilling, fae King of the Forgotten, can tame the most violent of beasts. Gearing for war, he is disciplined and focused, until a feral beauty wanders into his camp with a terrifying ability to sing monsters to life.